Firm heterogeneity and lobbying - Bretan, Pedro Luis Accioli Nobre (2006)
The structure of protection across sectors is usually interpreted as the result of competition among lobbies to influence politicians, but little attention has been devoted to the importance of individual firms in this process. This paper builds a model incorporating firm heterogeneity into a lobbying setup `a la Grossman and Helpman (1994), in a monopolistic competitive environment. We obtain that increased sectorial dispersion cause a fall in equilibrium tariff provided that the exporter’s cutoff is above the mean of the distribution. Also, higher average productivity brings about a fall in the equilibrium tariff, whereas an increase in export costs cause an increase in the tariff.